Coronary sinus anatomical features: Description and procedural implications during coronary sinus Reducer implantation. Issue 7 (19th November 2020) - Wilgenhof, Adriaan; Zivelonghi, Carlo; Verheye, Stefan; Vermeersch, Paul; Scott, Benjamin; Convens, Carl; Timmers, Leo; Leenders, Geert; Kuijk, Jan Peter Van; Stella, Pieter; Agostoni, Pierfrancesco
Abstract: Objectives: We hypothesized that some coronary sinus (CS) anatomies allow a more straightforward CS Reducer (CSR) implantation. Background: Recent decades have seen a rise in patients with chronic angina. When complete revascularization and maximal medical therapy fail to reduce symptoms, CSR has become a new therapeutic option. Methods: We identified a classical C‐shape—a near horizontal course of the proximal portion of a circular CS—in a retrospective analysis of 47 CSR implantations and compared the procedural time, fluoroscopic time, contrast use, presence of valves or bifurcations and procedural complications with the non‐C‐shape CS anatomy. Results: We found a significant difference in procedural (20.0 [19.0–24.7] min vs. 24.5 [20.7–51.0] min; p = .028 and fluoroscopic time (9.5 [7.5–14.5] min vs. 11.0 [7.9–30.0] min; p = .016). There was no significant difference in contrast use. The presence of bifurcations or valves along the CS course did not influence the procedural timings. Conclusion: This study is the first systematic evaluation of CS anatomy and its procedural implications. We identified a favorable C‐shape anatomy which allows for a more straightforward implantation. Operators should be aware of the different implications of CS anatomy, their influence on guiding catheter stability and overall procedure complexity.